The Implementation of Stay and Stray in Teaching Writing Hortatory Exposition Text - Edo Meggi Fernando (P-SEMART JOURNAL, 2022)
Writing skills are very important in learning English to make it easier for someone to exchange information or ideas with others. Thus, teachers also need interesting strategies for teaching writing. One strategy that can be used is stay and stray. This research investigates the implementation of stay and stray in teaching writing hortatory exposition. By using the observation checklist instrument, field notes, and question list, the researcher found that students could write exposition hortatory texts using sentence structures correctly in groups. In this activity, students are active and critical. At the final meeting students were asked to fill out a list of questions about their opinions related to stay and stray strategies in learning hortatory exposition writing. The findings showed that the percentage of students calculated higher scores is 78% and the lowest score of 22%. The students agreed that writing hortatory exposition using stay and stray was very interesting and enjoyable in the learning process. It can be concluded that the stay and stray strategy can help students to write hortatory exposition.